Kajian Kausalitas Tipologi Daerah Pesisir dan Pulau-Pulau Kecil Sebagai Paradigma Perubahan Pengelolaan Ekosistem Pesisir - Tahir (Jurnal Penelitian Pendidikan Geografi, 2023)
The polygenetic causal paradigm is the root cause of changes in coastal areas. The influence of human activities on mangrove ecosystems, especially land conversion, has an impact on changes in the area of mangrove forests and also affects the downstream of rivers. This study aims to 1) find the root causes of problems in coastal areas through the paradigm of polygenetic causality; and 2) utilization of coastal ecosystems through a dynamic equilibrium paradigm. This study uses a survey method to identify the main constituent materials of coastal areas, coastal relief, power, and energy processes that work in coastal areas and small islands in Kab. West Moon. Anthropodynamic and hydrodynamic factors have a major influence on the condition of the coastal areas and small islands of Kab. West Moon. Anthropodynamic factors can cause damage to mangrove ecosystems and coral reef ecosystems. Four principles related to effective coastal area management, namely: 1) an adaptive decision-making process; 2) introduction to the nature and special values regarding coastal areas; 3) a comprehensive strategy for integrating sectoral activities; and 4) emphasis on sustainable development. The dynamic equilibrium paradigm in the coastal areas and small islands of Kab. West Muna can be achieved if the utilization of coastal areas and small islands does not exceed their carrying capacity.